Revolving door laws and political selection - Raymond Fisman; Jetson Leder-Luis; Catherine O'Donnell; Silvia Vannutelli (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Revolving door laws restrict public officials from representing private interests before government after leaving office. While these laws mitigate potential conflicts of interest, they also may affect the pool of candidates for public positions by lowering the financial benefits of holding office. We study the consequences of revolving door laws for political selection in U.S. state legislatures, exploiting the staggered roll-out of laws across states over time. We find that fewer new candidates enter politics in treated states and that incumbent legislators are less likely to leave office, leading to an increase in uncontested elections. The decline in entry is particularly strong for independent and more moderate candidates, which may increase polarization. We provide a model of politician career incentives to interpret the results.
Keywords: D72; D73; K16; 330